KYRGYZ PEOPLE IN THE UZBEK ETHNIC COMMUNITY IN THE 19TH AND EARLY THE 20TH CENTURY - Abdullayev Ulug`bek Saydanovich (Journals Park Publishing, 2022)
This article about the history of Kyrgyz – Uzbek ethnic community in the late 19th- early the 20th centuries. It is shown that agricultural and ethnic community culture of Uzbek and Kyrgyz nations with the historical facts.
Keywords: ethnic; household culture; tribal